Effect of Job Involvement on Organizational Commitment: Evidence from Financial Institutions - Shrestha, Prakash; Parajuli, Dilip (Butwal Campus Journal, 2024)
The primary goal of this study was to assess the levels of job involvement and organizational commitment among employees involved in financial institutions, as well as to investigate the effect of job involvement on organizational commitment. A descriptive research design was adopted in this study. The study included 300 questionnaires delivered to 12 financial institutions (commercial banks, development banks, and finance companies). Out of them, only 179 (59.67%) were viable, and these were used for data analysis. The results presented that employees were judged to be highly involved in their jobs and committed to their institutions. Furthermore, it has been demonstrated that job involvement significantly and favorably affects commitment of employees. It indicates that employees who are more involved in their jobs have a stronger sense of commitment to their organizations. Therefore, Nepalese financial institutions must prioritize increasing job involvement and organizational commitment among their employees at all levels. Clear organizational goals provide greater possibilities for actively involved individuals to meet their needs and establish commitment to the organization. Financial institutions must adapt to these realities in order to foster a culture of involvement and commitment. Furthermore, employees should be encouraged to innovate and embrace creative working methods that are appropriate for different types of customers from all areas of society in order to maintain their growing interest and success in their jobs.